PENGOLAHAN AIR LIMBAH DOMESTIK DENGAN BIOSISTEM TANAMAN BASAH (CONTRUCTED WETLAND) DI BANDARA NGURAH RAI - Parasara, I Gusti Ngurah Bagus; Suyasa, I Wayan Budiarsa; Adhika, I Made (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 9 No 2 (2015), 2015)
Research has been conducted on domestic wastewater Ngurah Rai Wet Plant Biosystems (BTB) This study aims to determine the characteristics of the waste water, the effectiveness and capacity of the BTB’s decreased levels of BOD, COD and Ammonia. The experimental research method is using the media of sand and coral and plants Cattail. Data collection was performed every 6 hours for 48 hours and the pH, temperature, and analysis of BOD, COD, ammonia UPT done in the Bali Provincial Health Laboratory. Data were analyzed by descriptive statistics and regression .. The results showed that the initial wastewater characteristics exceed Standards of quality, effectiveness of the BBT in lowering BOD in wastewater WWTP Ngurah Rai have been effective (37.21%) of the Quality Standards (BM = 18.92 %), while the effectiveness of the process is still not less than 50% effective. As for changes in the levels of COD in a state that has not demonstrated effectiveness towards a decrease of 69.66% reduction in ammonia and BOD reduction in the highest capacity = 55.08 g . day. and ammonia = 42.24 g day. While in lowering the COD has not shown a decrease towards
Keywords: BTB; characteristics; effectiveness; capacity